ANALYSIS OF THE SYMBOLOGICAL SIGNIFICANCE OF THE HISTORY OF THE NATIONAL SKULLCAP BY REGION AND ITS REGULARITIES (Conference Zone, 2022)
This article explores the history of the Uzbek national skullcap. The symbolic meanings of patterns used on skullcaps by region are analyzed..